2006
DOI: 10.2174/138920106777549777
|View full text |Cite
|
Sign up to set email alerts
|

Does Isoform Diversity Explain Functional Differences in the 14-3-3Protein Family?

Abstract: The 14-3-3 family of proteins was originally identified in 1967 as simply an abundant brain protein. However it took almost 25 years before the ubiquitous role of 14-3-3 in cell biology was recognized when it was found to interact with several signalling and proto-oncogene proteins. Subsequently 14-3-3 proteins were the first protein recognized to bind a discrete phosphoserine/threonine-binding motifs. In mammals the 14-3-3 protein family is comprised of seven homologous isoforms. The 14-3-3 family members are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 60 publications
0
39
0
1
Order By: Relevance
“…Interaction of Rap1GAP2 and 14-3-3-All members for the 14-3-3 protein family are highly conserved and share high amino acid identity (30,31). With pulldown experiments we show that Rap1GAP2 binds to 14-3-3␤ and .…”
Section: Discussionmentioning
confidence: 84%
“…Interaction of Rap1GAP2 and 14-3-3-All members for the 14-3-3 protein family are highly conserved and share high amino acid identity (30,31). With pulldown experiments we show that Rap1GAP2 binds to 14-3-3␤ and .…”
Section: Discussionmentioning
confidence: 84%
“…14-3-3 (Ostrerova et al, 1999;Kleppe et al, 2001;Srivastava et al, 2002;Kjarland et al, 2006). Recently, Peng et al (2005) demonstrated that a functional interaction between ␣-synuclein and PP2A can regulate TH phosphorylation and TH activity.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, we showed that ␣-synuclein interacts with PKC␦ and regulates its activity after neurotoxic insults (Kaul et al, 2005). Therefore, in the dopaminergic system, the physical and functional association between PKC␦, TH, and PP2A could be facilitated and/or regulated by chaperone proteins such as ␣-synuclein (Kaul et al, 2005;Peng et al, 2005) and14-3-3 (Ostrerova et al, 1999;Kleppe et al, 2001;Kjarland et al, 2006). Nevertheless, additional studies are required in both in vitro and in vivo model systems to elucidate the dynamics of physical and functional regulation of PKC␦ and PP2A in regulation of TH activity.…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3 proteins are involved in a range of cellular processes including the regulation of enzyme activity, stimulation of protein-protein interactions, and the localization and function of ion channels. 93,94 ERretained GluK5 appears to be bound to COPI, whereas subunit assembly with GluK2 releases GluK5 from the ER and increases its interaction with 14-3-3ζ and subsequent surface expression 81 suggesting that the ER retention signals are masked following oligomerization and highlighting how correct receptor assembly can lead to the switching of interacting partners to regulate a trafficking checkpoint within the biosynthetic pathway.…”
Section: -3-3 Proteins and Copimentioning
confidence: 99%